THE IMPORTANCE OF COMMUNICATIVE COMPETENCE IN TEACHING ENGLISH LANGUAGE (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2025)
Communicative competence plays a pivotal role in the effective teaching and learning of the English language. It encompasses linguistic, sociolinguistic, discourse, and strategic competencies, enabling learners to use the language appropriately in diverse contexts. This competence fosters meaningful interactions, enhances language proficiency, and facilitates cultural understanding. The integration of communicative approaches in language instruction empowers students to develop fluency, accuracy, and confidence in real-life communication. This paper explores the significance of communicative competence in English language teaching, emphasizing its impact on learner engagement, motivation, and overall language acquisition.